Monoamniotic Monochorionic Twins Discordant for Noncompaction Cardiomyopathy - Ng, Dianna (2013)
Occasionally “identical twins” are phenotypically different, raising the question of zygosity and the issue of genetic versus environmental influences during development. We recently noted monochorionic-monoamniotic twins, one of which had an isolated cardiac abnormality, noncompaction cardiomyopathy, a condition characterized by cardiac ventricular hypertrabeculation. We examined the prenatal course and subsequent pathologic correlation since ventricular morphogenesis may depend on early muscular contraction and blood flow. The monochorionic-monoamniotic female twin pair was initially identified since one fetus presented with increased nuchal translucency. Complete heart block was later identified in the fetus with nuchal translucency who did not survive after delivery. In contrast, the unaffected twin had normal cardiac studies both prenatally and postnatally. Pathologic analysis of the affected twin demonstrated noncompaction of the left ventricle with dysplasia of the aortic and pulmonary valves. Dissection of the cardiac conduction system disclosed atrioventricular bundle fibrosis. Maternal lupus studies, amniocentesis with karyotype, and studies for 22q11.2 were normal. To test for zygosity, we performed multiple STR marker analysis and found that all markers were shared even using non-blood tissues from the affected twin. These studies demonstrate that monozygotic twins that are monochorionic monoamniotic can be discordant for cardiac noncompaction. The results suggest further investigation into the potential roles of pathologic fibrosis, contractility, and blood flow in cardiac ventricle development.